Penggunaan Media Pembelajaran Berbasis ICT Dan Pengaruhnya Terhadap Tingkat Kelulusan Ujian Nasional Siswa Pada Sekolah Menengah Di Kota Palopo (Studi Kasus Di 5 Sekolah Menengah Di Kota Palopo) - Rosdiana Rosdiana (Al-Khwarizmi : Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2016)
Mastery of ICT in the professional work of faculty strongly supports the effectiveness and success in implementing tasks facultys ability to understand and apply ICT-based learning media is diverse, so the effect is given to student learning outcomes also vary. This study also aims to provide information to the perpetrators of the educators extent of influence the application of ICT-based learning media to encourage them to improve their skills and their professionalism as teachers in developing instructional media used. Media ICT-based learning affects the learning outcomes of students in a particular class of National Examination in three (3) years) this. From the description of the data we collect see the value of the average results of students of National Examination within three (3) years in five (5) secondary school located in the town of Palopo and the type of media used by teachers, it appears that there tend to be differences in test scores better for students whose teachers use ICT-based learning media compared to teachers who do not use ICT.